Children Need Clean Water to Grow : E. Coli Contamination of Drinking Water and Childhood Nutrition in Bangladesh - Joseph, George (World Bank, Washington, DC, 2019)
Water, sanitation, and hygiene interventions are increasingly recognized as essential for improving nutritional outcomes in children. Emerging literature describes the negative effects of poor sanitation on child growth. However, limited evidence has shown a link between water quality and nutritional outcomes. Similar to poor sanitation, it is plausible that water contaminated with E. coli could affect the nutritional status of children through various possible biological pathways, such as repeated episodes of diarrhea, environmental enteropathy, parasites, or other mechanisms that inhibit nutrient uptake and absorption. This study explores the relationship between contaminated water and stunting prevalence among children younger than age five years, using unique cross-sectional data from the 2012–13 Bangladesh Multiple Indicator Cluster Survey, which was one of the first nationally representative surveys to include water quality testing for E. coli. E. coli contamination in drinking water is measured at household and source points. Stunting is measured using height-for-age z-scores for children under five, where a child is considered stunted when he or she is two or more standard deviations below the median of the World Health Organization reference population. The results of multiple probit regression models indicate a 6 percent increase in the prevalence of stunting in children who are exposed to highly contaminated drinking water at household point compared with those exposed to low-to-medium contamination. When contamination is measured at the source level, the association is greater, with a 9 percent increase in the likelihood of stunting when exposed to a high level of contamination.